Multi-run Operational Modal Analysis of the Guadiana cable-stayed bridge - Bart Peeters (2006)
Ambient vibration measurements of the International Guadiana Bridge are used to validate different methods for so-called multi-run Operational Modal Analysis. The bridge was measured in 28 runs, keeping some reference sensors at fixed locations while others were positioned at a different location in each run. Measuring all runs took more than 2 days and it was observed that in this period, the wind and traffic excitation was changing very significantly. The reference sensors have to be used in some sense to compensate for this non-stationary excitation. In the most traditional method, each run is analysed independently and, afterwards, the analysis results are combined to yield a global set of modal parameters. Another possibility that will be explored in this paper is to combine the data first and then only a single modal analysis need to be performed. Also in this paper, different modal parameter estimation methods will be assessed: the operational PolyMAX method will be compared to Stochastic Subspace Identification.